2016
DOI: 10.1016/j.appet.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging children to eat more fruit and vegetables: Health vs. descriptive social norm-based messages

Abstract: Traditional intervention approaches to promote fruit and vegetable consumption outline the health benefits of eating fruit and vegetables. More recently, social norm-based messages describing the healthy eating habits of others have been shown to increase fruit and vegetable intake in adults. Here we report two experimental studies which investigated whether exposure to descriptive social norm-based messages about the behaviour of other children and health-based messages increased fruit and vegetable intake in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 43 publications
(93 reference statements)
1
38
0
2
Order By: Relevance
“…Other similar studies have reported that social norm‐based messages are effective in reducing actual intake of ‘junk’ food in adults in the laboratory (Robinson et al . ) and can promote the consumption of vegetables by children (Sharps & Robinson ). In addition, it has been reported that a social norm intervention targeting fruit and vegetable intake resulted in an increase in skin carotenoids, an indicator of carotenoid‐containing fruit and vegetable intake over 8 weeks (Wengreen et al .…”
Section: Social Norms and Their Influence On Eatingmentioning
confidence: 99%
“…Other similar studies have reported that social norm‐based messages are effective in reducing actual intake of ‘junk’ food in adults in the laboratory (Robinson et al . ) and can promote the consumption of vegetables by children (Sharps & Robinson ). In addition, it has been reported that a social norm intervention targeting fruit and vegetable intake resulted in an increase in skin carotenoids, an indicator of carotenoid‐containing fruit and vegetable intake over 8 weeks (Wengreen et al .…”
Section: Social Norms and Their Influence On Eatingmentioning
confidence: 99%
“…For example, learning that others in a laboratory study have been eating a lot of food typically results in participants increasing their food intake (Prinsen et al, 2013; Robinson and Field, 2015). Likewise, it has been shown that if children are led to believe that their peers are eating a lot of vegetables they increase their own consumption of vegetables (Sharps and Robinson, 2015, 2016). A smaller number of intervention studies have examined whether providing consumers with information about descriptive peer norms influences future consumer behavior measured immediately afterwards or up to 1 week later, but results have been mixed (Stok et al, 2012; Mollen et al, 2013; Robinson et al, 2013b, 2014a; de Bruijn et al, 2015; Verkooijen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…That is, selected peers were secretly instructed to promote water drinking by increasing their own water drinking behavior and talking about the benefits of water drinking to others, which increased water drinking and decreased the consumption of sugar-sweetened beverages among their class mates. Other experimental studies found that adolescents increased their vegetable intake after exposing them to information about the amount that their peers ate (21,22). In addition, an online study found that an injunctive peer norm promoting fruit and vegetable intake was associated with higher self-reported fruit and vegetable intake as well as lower unhealthy snack food intake (19).…”
Section: Introductionmentioning
confidence: 98%